Relationship of Knowledge of Breastfeeding Mothers with Attitude to the Provision of the Covid-19 Vaccine at Puskesmas Bintang Aceh Central Regency Year 2022 - Febriana Sari Sari; Fitriyani S Yoga (Science Midwifery, 2022)
A breastfeeding program with the slogan "Love Babies, Give ASI" has been launched by the government. However, the coverage of ASI has not reached the national target. 80%. One of the causes of the failure of exclusive breastfeeding is due to the problem of adequacy of breast milk. Neck massage is believed to help expel breast milk. The purpose of this study was to examine the effectiveness of neck massage on increasing the amount of postpartum breast milk from the first day to the third day. This type of research is quantitative with the static group comparison research design. The sampling technique used is Systematic Propionate Random Sampling. The sample in this study was 52 and the sample per group was 26 respondents. The population members affected by the sample in PMB A are patients whose number is multiple of 2, and PMB B is multiple of 2. The results of the study of the effect of neck massage on increasing the amount of postpartum breast milk on the first to third day from the analysis of comparative data of the experimental group and the comparison group obtained p -value 0.000, meaning that neck massage is more effective than pectoralis major muscle massage in increasing breast milk production in postpartum mothers on the first to third day. Therefore, health workers, especially physiotherapists, make neck massage in breast care for postpartum mothers with complaints of breast milk not coming out and teach mothers and families how to massage the neck properly and correctly